Pengaruh Penggunaan Teknologi Informasi Dan Kemampuan Berkomunikasi Interpersonal Terhadap Kinerja Karyawan - Vandela, Fransiska; Sugiarto, Agus (Jurnal Manajemen, 2021)
Information and communication technology is used in all areas of human life, including in a company. Utilization of technology aims to improve employee performance. In addition, employee performance is believed to be related to their ability to carry out interpersonal communication activities. The main purpose of this research is to analyze the influence of the use of information technology and interpersonal communication skills on employee performance . This analysis is used to test the relationship between independent variables namely the use of information technology (X1), interpersonal communication skills (X2) with the dependent variable namely employee performance (Y). Likert scale as the assessment scale used. The number of samples used was 58 respondents with saturated sampling techniques. This research method uses multiple regression analysis. Data obtained by distributing questionnaires. Based on the results of this study indicate that the variable use of information technology and interpersonal communication skills have a positive effect on employee performance.